Implementasi Layanan Penempatan dan Penyaluran terhadap Pengambilan Keputusan Pemilihan Jurusan Studi - Rosalinda; Yarmis Syukur; Dina Sukma (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Placement and distribution services are planned and systematic efforts to support students to get positions that match their talents, interests, and abilities. Through this service, students can avoid mismatches between their potential and conditions in making decisions about study programs, so that they can function optimally. This study uses a literature study method. This article discusses placement and distribution services in counseling guidance, which play an important role in helping students choose study programs that match their potential, interests, and talents. This service not only provides information on study programs, but also supports decision making that is in line with career goals.